Identification of HR Management Strategies for Small Business Disrupted by COVID-19: Marketing Literature Review - Rudianto, Rudianto; Bangkara, B.M.A.S. Anaconda; Kurniawan, I Made Gede Ariestova; Satmoko, Nugroho Djati; Hendriarto, Prasetyono (Budapest International Research and Critics University, 2021)
The main objective of this study is to identify HR management techniques for small companies affected by the epidemic, which is still a topic of much discussion in the media. We conducted a series of data studies on various well-known journal publishing data sources, including Google Books, Elsevier, Taylor&Francis, sage pub, Academic research, and other online sources, to ensure smooth identification and reporting in the form of descriptive discussions. Electronic data solutions are the ideal choice in this pandemic disruption when public mobility is not possible. The data review process includes several stages, such as initial reading to understand, coding system, and evaluation of data with high interpretation with a phenomenological approach to quickly draw conclusions that answer research questions with valid and reliable values. The results include that the HR management strategy for increasing productivity in small businesses is that small businesses also need a strategy to increase their human resources. These small businesses also have the vision to achieve profits and help absorb labor and reduce unemployment.